PERAN PENYULUH PERTANIAN LAPANGAN DALAM MENINGKATKAN PRODUKSI PADI SAWAH (Oryza sativa L.) DI KELURAHAN PULAU ATAS KECAMATAN SAMBUTAN KOTA SAMARINDA (The Role of Field Agriculture Instructor to Increase Wetland Paddy Production (Oryza sativa L.) in Pulau Atas Urban Village Sambutan Subcity Samarinda City) - ANAS ANAS; JURAEMI JURAEMI (Universitas Mulawarman (University of Mulawarman), 2020)
The increase of wetland paddy production (Oryza sativa L.) is influenced by the activity of counseling by Field Agriculture Instructor (FAI). This study aimed to know the role of FAI to increase wetland paddy production in Pulau Atas Urban Village, Sambutan Subcity, Samarinda City. This research was carried out during four months from August to September 2017. Determination of respondent number was done by proportional random sampling method with the number of respondents of 31 farmers. The role of FAI to increase wetland paddy production was known by Chi Square test. The research results show FAI has role to increase wetland paddy production (Oryza sativa L.) in Pulau Atas Urban Village, Sambutan Subcity, Samarinda City, based on the result of data analysis that showed χ2calculate (36.07) > χ2table (5.59).